Feasibility, safety, and outcome of fetoscopic endoluminal tracheal occlusion for severe congenital diaphragmatic hernia at a low case-load center: one center's experience - Saud Alshanafey; Wesam I. Kurdi; Maha Tulbah; Rubina MA Khan; Nada Al Sahan; Maisoon Al Mugbel; Fahad Al-Hazzani; Gawaher Almutairi; Ala Jebreel; Maha Al-Nemer (Annals of Saudi Medicine)
BACKGROUND: Antenatal fetoscopic endoluminal tracheal occlusion (FETO) has been introduced as an effective intervention to improve the outcome of severe congenital diaphragmatic hernia (CDH). OBJECTIVE: We report our early experience with FETO. DESIGN: A retrospective chart review of case series. SETTING: Tertiary health care center. PATIENTS AND METHODS: 18–45 years old, with single fetuses diagnosed with left severe CDH (lung-head ratio <1 measured between 27–29 weeks of gestational age (GA) and liver up or observed/expected lung-to-head ratio <25%, normal echocardiogram and karyotype were included. FETO was performed between 28–30 weeks of gestation and removed after 4–6 weeks or at birth during an ex utero intrapartum treatment (EXIT) procedure. MAIN OUTCOME MEASURES: FETO represents a viable option for severe type of CDH fetuses with reasonable outcomes. FETO performance in low volume centers may be feasible with reasonable outcomes. Good outcome of postnatal care with no potential antenatal complications may affect FETO adoption in some societies. SAMPLE SIZE: 5 RESULTS: 14 pregnant women were referred for assessment and only 7 met the inclusion criteria. Two were excluded initially (late referral and spouse refusal) and a 3rd excluded later due to failure of FETO due to faulty balloons. The median age of the mothers was 28 years and the gestational age was 29 weeks. Median observed/expected lung-to-head ratio was 23%. Among patients who had successful FETO, one had the balloon removed fetoscopically 4 weeks after insertion and one was removed 8 weeks after insertion during an elective EXIT procedure and both have survived. The other two had premature labor after 1 and 5 weeks after FETO and balloon removed during an emergency EXIT procedures, and both died within 24 hours of birth. CONCLUSION: FETO represents a viable option for severe type of CDH fetuses with reasonable outcome. FETO performance in a low volume centers may be feasible with reasonable outcomes. Good outcome of postnatal care with no potential antenatal complications may affect FETO adoption in some societies. LIMITATIONS: Retrospective nature of the study may imply inaccuracy, but we believe data from electronic medical records is highly accurate.